Impact of plerixafor (mozobil) on hospital efficiency: A single center experience. Issue 1 (28th April 2017) - Azar, Nabih; Ouzegdouh, Maya; Choquet, Sylvain; Leblond, Véronique
Abstract: Plerixafor (Mozobil) in combination with granulocyte colony‐stimulating factor (G‐CSF) has shown to increase mobilization of peripheral blood stem cells (PBSC) as compared to G‐CSF alone in patients undergoing autologous stem cell transplantation (ASCT). However, up to 25% of patients treated with G‐CSF alone still fail mobilization. Adding plerixafor to poor mobilizers allows to rescue these patients from mobilization failure and to reduce the number of apheresis sessions. The goal of this retrospective study was to capture the impact of plerixafor on treatment outcome and on apheresis department efficiency. The latter was measured in terms of time‐slots lost, that is, the number of apheresis sessions scheduled but not carried out due to poor mobilization, and the number of elective apheresis sessions performed for patients undergoing extracorporeal photopheresis (ECP). Hospital records of patients treated before and after introduction of plerixafor were collected and analyzed. With plerixafor, the mobilization failure rate dropped from 12% to 4% and the mean number of time‐slots lost per patient dropped from 1.39 to 0.89. Additional drug costs due to plerixafor were partially balanced by a reduction in apheresis sessions, resulting in an additional cost of 759€ per ASCT candidate. More importantly, with the use of plerixafor, the availability of time‐slots turned from erratic to predictable such that freed capacity could be dedicated to other apheresis procedures. As a result, the number of ECP sessions increased from 0 in 2005 to 685 sessions in 2014.